2019
DOI: 10.30827/publicaciones.v49i4.11736
|View full text |Cite
|
Sign up to set email alerts
|

Aprendizaje-servicio y desarrollo de la expresión corporal en la formación del profesorado de educación infantil

Abstract: El proyecto EXCORAS se desarrolla en el grado en maestro de educación infantil. El objetivo de este trabajo es mostrar el nivel de satisfacción de los estudiantes universitarios en relación a los aprendizajes extraídos en el proyecto. Para ello, utilizaremos una metodología mixta con varios instrumentos: Escala Osgood y entrevistas semiestructuradas a los agentes implicados. En definitiva, terminamos señalando que los estudiantes que participan en proyectos de ApS incrementan sus oportunidades de adquirir una … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 7 publications
1
6
0
2
Order By: Relevance
“…Our results reinforce findings from previous studies such as Chiva-Bartoll and Gil-Gómez (2018); Rodríguez-Izquierdo (2018), andSotelino et al (2019), in which they concluded that service-learning notably facilitates the achievement of professional action skills in higher education institutions. This consistency means that we have a measuring instrument that can be used to check the acquisition of competencies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results reinforce findings from previous studies such as Chiva-Bartoll and Gil-Gómez (2018); Rodríguez-Izquierdo (2018), andSotelino et al (2019), in which they concluded that service-learning notably facilitates the achievement of professional action skills in higher education institutions. This consistency means that we have a measuring instrument that can be used to check the acquisition of competencies.…”
Section: Discussionsupporting
confidence: 91%
“…It is therefore an educational strategy with great potential to facilitate access to employment (Gallagher, 2007;Rodríguez-Izquierdo, 2018). Sotelino et al (2019) emphasized the notable impact of the service-learning methodology on participants and the community, with the greatest effects being in higher education (Chiva-Bartoll and Gil-Gómez, 2018). In addition, Santos-Rego et al (2015) reiterated the suitability of service-learning for addressing the educational process in a comprehensive manner, from the acquisition of cognitive and academic skills to civicsocial skills.…”
Section: Service-learning Development Of Generic Competencies and Employabilitymentioning
confidence: 99%
“…On the other hand, moving now to the quantitative investigations or the quantitative part of those using mixed methods, a very recurrent research instrument was questionnaires [ 28 , 30 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. The validated questionnaires used were the Entrepeneurship Competency Scale [ 51 ], the Subjective Happiness Scale [ 28 ], and the Multidimensional Attitudes Scale Toward Persons With Disabilities questionnaire [ 29 ], among others.…”
Section: Resultsmentioning
confidence: 99%
“…Following Rubio and Escofet [ 61 ], we established the following basic categories of limitations: Basic dynamisms. This type of limitation may encompass, educators’ limited training and experience regarding SL [ 45 , 46 ], limited time of engagement in the program on the part of participants [ 27 , 50 ], and difficulties when adjusting the service to the specific needs of the social community [ 41 ], or the intrinsic difficulties coming with the features of the people receiving the service [ 27 ]. Pedagogical dynamisms.…”
Section: Resultsmentioning
confidence: 99%
“…To minimize the negative consequences for the body associated with the improper physical education of the child, it is necessary to teach him how to handle his body correctly from childhood, which in the future will allow him to develop harmoniously. (LIROLA et al, 2020;SOTELINO, 2019). The issues of promoting a healthy lifestyle are of concern to both specialists and the population as a whole, which is confirmed by the totality of studies carried out in various scientific fields (BRONNIKOVA et al, 2020).…”
Section: Discussionmentioning
confidence: 97%